SIDNFF: Source identification network forensics framework for cloud computing - Khan, S.; Gani, Abdullah; Abdul Wahab, A.W.; Bagiwa, M.A. (2015)
This paper presents a novel framework for network forensics in cloud computing (CC). The framework investigates malicious activities performed by an intruder while affecting virtual machine on same or another cloud resource (CR). Moreover, it investigate malicious activities of intruders by determining its source while keeps privacy for cloud users with out losing their data confidentiality. Our proposed framework provides initial foundations to create real network forensics model for CC in a right essence.